An On-Demand Oxygen Flow Meter for Enhanced Patient Comfort and Reduced Oxygen Cost in Hospitals. Issue 1 (31st December 2022) - Derom, Eric; Meijer, Eduard J.; Van Enschot, J. W. T.
Abstract: Background: Hypoxemia is currently treated in hospital wards with oxygen, released continuously by "conventional" flow meters. A new type of hybrid flow meter allows to switch between on-demand and continuous mode. The aim of this observational study was to assess whether this new device reduces oxygen expenditure, is well accepted in a hospital setting and improves patient comfort during oxygen therapy. Methods: Oxygen was administered in hypoxemic patients with conventional or hybrid flow meters to maintain an oxygen saturation of ≥ 92% over a 12-week period. Every two weeks conventional and hybrid flow meters were switched. The overall oxygen delivery to the ward was continuously measured with a data logging device installed in the main oxygen pipeline and corrected for multiple confounding factors. Humidity measurements, for which a sensor placed in front of one of the nostrils, and patient questionnaires, were used to assess patient comfort during continuous and on-demand flow. Results: Overall oxygen delivery decreased by 39% when switching from continuous flow to on-demand therapy after correction for confounding factors. Continuous flows significantly decreased relative humidity more than equivalent on-demand settings and the latter tended to increase comfort. Conclusions: Hybrid flow meters cause a significant reduction in oxygen delivery in a hospital ward, which may lead to financial savings. Using the on-demand technology also lowers the dryness of the upper airways (and may increase patient comfort), while maintaining an adequate oxygenation.